1965
DOI: 10.1021/je60027a012
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpies, Entropies, and Free Energy Functions of TIF, TIBr, and TII above Room Temperature.

Abstract: The enthalpy increments above 298°K. for solid and liquid thallous fluoride, bromide, and iodide were measured with a drop calorimeter. These data together with literature values for the absolute entropies were used to calculate the enthalpy, entropy, and free energy for these compounds. The thermodynamic functions for the gaseous phases of these compounds were calculated from molecular constant data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1967
1967
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Numerous x-ray studies of CdS [49,68,98,118,146] have confirmed the high pressure structure as cubic NaCl-type. Most of these studies were performed in situ.…”
Section: Zinc Oxidementioning
confidence: 99%
“…Numerous x-ray studies of CdS [49,68,98,118,146] have confirmed the high pressure structure as cubic NaCl-type. Most of these studies were performed in situ.…”
Section: Zinc Oxidementioning
confidence: 99%
“…However, space group P2cm requires there to be two symmetry-independent pairs of anions and cations in 2c x,y, sites (labeled Tl1, Tl2, F1, and F2), this structure being identical to the Pbc2 model of Barlow and Meredith (11) if the ionic coordinates satisfy the conditions y 2 "!y 2 and y $ "!y $ . On increasing temperature a structural transition has been observed at &355 K by di!erential thermal analysis (DTA) (9), drop calorimetry (15), and X-ray di!raction (11) methods. The structure of the high-temperature modi"cation [labeled TlF-I (9)] has been studied by X-ray di!raction and the results are summarized in Table 1.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…--Enthalpy measurements above 298 ~ to about 1000~ were measured in a drop calorimeter by the same method as described earlier (12,13). The sample of about 10g of BiF3 was placed in a platinum test tube and the end sealed by crimping and platinum soldering.…”
Section: Properties Of Bif3 1139mentioning
confidence: 99%